Therapeutic plasma exchange for the treatment of systemic sclerosis: A comprehensive review and analysis. Issue 2 (June 2018) - Harris, Edward S; Meiselman, Herbert J; Moriarty, Patrick M; Metzger, Allan; Malkovsky, Miroslav
Background: Therapeutic plasma exchange has been tried as a treatment approach for systemic sclerosis since 1978 based on the rationale that some circulating factor is involved in disease pathogenesis, for example, autoantibodies or immune complexes, and that removing the potential pathogenic factors could lead to symptom improvement. Based on our impression that clinicians and researchers are largely unaware that a large volume of research has been published about the use of therapeutic plasma exchange as a treatment for systemic sclerosis, we conducted a comprehensive review and analysis of all published research on this topic. Results: We identified 46 relevant articles that met our search criteria, involving a total of 572 patients. Of these, 19 were case studies; the rest ranged from small observational studies to prospective randomized clinical trials. In all but two studies, most patients receiving therapeutic plasma exchange showed improvements in both clinical symptoms and laboratory markers, including significant improvement in Raynaud's symptoms and healing of digital ulceration after three to four weekly treatments. The beneficial effects from even a short course of therapeutic plasma exchange treatments were long-lasting, typically 6 months or longer. Therapeutic plasma exchange was very well tolerated. Adverse events were rare and, in almost all cases, mild and transitory. Conclusion: These results suggest that long-term therapeutic plasma exchange may offer a low-risk way to control and in some cases reverse systemic sclerosis symptoms. The mechanism for the clinical improvements seen from therapeutic plasma exchange in systemic sclerosis patients is unclear. Therefore, additional studies of therapeutic plasma exchange effects in systemic sclerosis appear to be highly desirable.